ChemInform Abstract: Phenolic Constituents from the Rhizomes of Acorus gramineus and Their Biological Evaluation on Antitumor and Antiinflammatory Activities. Issue 7 (22nd February 2013) - Kim, Ki Hyun; Moon, Eunjung; Kim, Ho Kyung; Oh, Ju Yeoun; Kim, Sun Yeou; Choi, Sang Un; Lee, Kang Ro
Abstract The bioassay‐guided fractionation of the methanolic extract of the title plant leads to isolation and identification of thirteen phenolic derivatives, including the new neolignans surinamensinol A (I) and B (II) and the new phenolic compound acoramol (III).